Aspects related to variability of radiative cooling by NO in lower thermosphere, TEC and O/N2 correlation, and diffusion of NO into mesosphere during the Halloween storms. Issue 1 (1st January 2023) - Ranjan, Alok Kumar; Sunil Krishna, M.V.; Kumar, Akash; Sarkhel, Sumanta; Bharti, Gaurav; Bender, Stefan; Sinnhuber, Miriam
Abstract: Nitric Oxide is a very important trace species which plays a significant role acting as a natural thermostat in Earth's thermosphere during strong geomagnetic activity. In this paper, we present various aspects related to the variation in the NO Infrared radiative flux (IRF) exiting the thermosphere by utilizing the TIMED/SABER (Thermosphere Ionosphere Mesosphere Energetics and Dynamics/ Sounding of the Atmosphere using Broadband Emission Radiometry) observational data during the Halloween storm which occurred in late October 2003. The Halloween storm comprised of three intense-geomagnetic storms. The variability of NO infrared flux during these storm events and its connection to the strength of the geomagnetic storms were found to be different in contrast to similar super storms. The connection between the quantum of energy outflux from the upper atmosphere into space in terms of NO IRF and the duration of storms is established. The NO radiative cooling, and the closely correlated depletion in O/N2 ratio are controlled by the Joule heating intensity (proxied by AE-index). The collisional excitation rate of NO, calculated using the modelled datasets of WACCM-X (Whole Atmosphere Community Climate Model with thermosphere and ionosphere extension), correlates well with the observed pattern of radiative emission by NO. Observational datasets from TIMED/GUVI (Global Ultra-Violet Imager) and MIT Haystack observatory madrigal GNSS (Global navigation satellite system) total electron content (TEC) database shows that the TEC and O/N2 enhancement in low-mid northern hemispheric latitudes are mainly controlled by the z-component of Interplanetary magnetic field (IMF-B z ). The penetration of eastward electric field during the storm events is found to be responsible for the overall enhancement of TEC. The contribution of enhanced day-side TEC in observed variation of O/N2 ratio by GUVI is also reported. It is also seen that during substorms related events the night-time polar region experiences more cooling due to NO than the daytime polar region. The connections between the mid- and low-latitude enhancement in NO IRF with the propagation of LSTIDs (Large-scale traveling ionospheric disturbances) in combination with the O/N2 variability, and the altitudinal variation in NO flux with the progression of the storm is also investigated. This study presents the evidence on the role of diffusion processes in the large scale enhancement of NO in the mesospheric altitudes.